2013
DOI: 10.1007/s12160-013-9526-2
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Dampening in Persons with Elevated Blood Pressure: Affect Dysregulation and Risk for Hypertension

Abstract: Cardiovascular emotional dampening is independent of alexithymia and affect in men. Dampened emotion recognition could potentially influence interpersonal communication and psychosocial distress, thereby further contributing to BP dysregulation and increased cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
57
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(62 citation statements)
references
References 40 publications
3
57
0
2
Order By: Relevance
“…Though seemingly counterintuitive, the current findings follow the long-standing association between BP and sensitivity to physical pain (Bruehl & Chung, 2004) and recognition of emotional stimuli (McCubbin et al, 2014; Pury et al, 2004). The former specifically suggests that higher, rather than lower, BP may have functional significance for both physical and social pain (Dworkin, 1988; Dworkin et al, 1979).…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Though seemingly counterintuitive, the current findings follow the long-standing association between BP and sensitivity to physical pain (Bruehl & Chung, 2004) and recognition of emotional stimuli (McCubbin et al, 2014; Pury et al, 2004). The former specifically suggests that higher, rather than lower, BP may have functional significance for both physical and social pain (Dworkin, 1988; Dworkin et al, 1979).…”
Section: Discussionsupporting
confidence: 66%
“…Thus, higher resting blood pressure has been related to reduced valence and arousal ratings of both negative and positive images from the International Affective Picture System (IAPS; Pury, McCubbin, Helfer, Galloway, & McMullen, 2004). Similar findings were observed in a separate study examining blood pressure and intensity ratings of stimuli with emotional content (sentences and facial expressions; McCubbin et al, 2014). To the extent that social pain from perceiving threats to one’s social value from others is similar to emotional experiences from witnessing emotional content, then this work may further suggest a potential negative relationship between resting blood pressure and sensitivity to social pain.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…Several recent studies have shown that elevated resting BP is related to a more general dampening of emotional response to a variety of aversive stimuli. For example, resting BP has significant correlations with emotional responses to evocative photographic scenes (Pury, McCubbin, Helfer, Galloway, & McMullen, ) and perception of emotions in facial expressions and written narratives (McCubbin et al, ). This BP‐associated emotional dampening may be one mechanism by which resting BP is associated with subjective reports of pain.…”
mentioning
confidence: 99%